(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Hyperprolactinemia is one of the most significant endocrine causes of primary infertility in women. Elevated prolactin levels disrupt the hypothalamic–pituitary–ovarian axis, leading to ovulatory dysfunction, menstrual irregularities, and infertility. Early diagnosis and optimized treatment strategies are essential for restoring reproductive function. This study was conducted at the Khorezm branch of the Republican Specialized Scientific and Practical Medical Center of Endocrinology and aimed to evaluate the clinical and hormonal characteristics of women with primary infertility associated with hyperprolactinemia, as well as to optimize therapeutic approaches. The results demonstrate that individualized dopamine agonist therapy significantly improves hormonal balance, ovulatory function, and fertility outcomes.